Tetramethylenedisulfotetramine: A Health Risk Compound and a Potential Chemical Warfare Agent - Patocka, Jiří; Franca, Tanos C C; Wu, Qinghua; Kuca, Kamil (Toxics, 2018)
Tetramethylenedisulfotetramine (TETS, tetramine) is a toxic organic compound that is used as an effective rodenticide. However, this neurotoxin is not only toxic to rodents, it also causes poisoning in humans. Due to its high level of toxicity for humans, the use of TETS as a rodenticide has been banned and its production has been discontinued. Despite this, human poisoning by this substance is unfortunately still very common. The largest number of poisonings are reported in China, but in the United States, dozens of poisonings still happen annually. TETS is one of the most hazardous pesticides and also a possible chemical warfare agent with no known antidote. In this article, we aim to summarize the biochemical and toxicological data of TETS and hope to cast some light on the toxicological risk to human health.
Keywords: pesticide; TETS; Tetramethylenedisulfotetramine; rodenticide; chemical warfare agent